Vegetables - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Weed specialist Dr David Mburu advises vegetable farmers on the use of herbicides and the importance of good seed bed preparation.